OBTENÇÃO DE NANOPARTÍCULAS COM SUPERFÍCIE BIOATIVA PARA USO EM PELÍCULAS PROTETORAS DE ALIMENTOS - PELISSARI, Karmel P.; DIAS, Fabricia E. M.; OLIVEIRA, Ariana A. F. de; KURAMOTO, Mariana Y. S.; BEZERRA, Felipe M.; RODRIGUES, Daniela C. M. (ANAIS DO ENIC, 2018)
-